A Critical Legal Analysis on the Reasons for the Continous Occurence of Cases of Sexual Harrasment at Work and Its Effects on the Victims - Shakira Mukera (Uganda Christian University, 2025)
Sexual harassment remains one of the least acknowledged, yet common practices experienced within employment in Uganda. It takes the form of any sexual behavior whether intended or not that is viewed as offensive by the victim party. Until 2006, there had been no clear attempts developed in the combating of this practice which had consistently jeopardized the wellbeing and working life of employees as well as equality at the workplace. This gap raised concerns not only for the legal authorities but also for the employers and the aggrieved parties since there were no clear measures on how the subject was to be addressed. Henceforward with the later emergence and development of the legal regime on employment, fair means of protection were introduced towards combating this practice. To achieve this, these laws worked towards promoting equality of opportunity in employment as established under Article 40(a) of the Uganda Constitution and this involved creating fair employment grounds in as far as recruitment, promotion, remuneration and termination were concerned. However, despite signifying the importance of equality of opportunity towards combating sexual harassment, these laws have so far remained less progressive in achieving this objective. This is attributed to the many gaps existent therein and the poor enforcement mechanisms adopted in giving effect to these laws. Therefore this research serves to show reasons for the continuous occurrence of sexual harassment at work places despite the existence of various measures prohibiting it and the effects it has on those who experience it
Under Graduate Research